Copper- and ligand-free sonogashira reaction catalyzed by Pd(0) nanoparticles at ambient conditions under ultrasound irradiation - Gholap, Atul R.; Venkatesan, K.; Pasricha, R.; Daniel, Thomas; Lahoti, Rajgopal J.; Srinivasan, K. V. (Journal of Organic Chemistry, 2005)
The Sonogashira reaction proceeds at ambient temperature (30 degrees C) in acetone or room-temperature ionic liquid, 1,3-di-n-butylimidazolium tetrafluoroborate ([bbim]BF4), as solvent under ultrasound irradiation to give enhanced reaction rates, excellent chemoselectivity, and high yields in the absence of a copper cocatalyst and a phosphine ligand. TEM analysis showed the formation of stable, crystalline, and polydispersed Pd(0) nanoparticles as catalyst for the reaction.